Business and Artistic Legitimacy in Antioqueña Advertising 1920–1930 (2024)
ABSTRACT: In the Colombian case, in the twenties of the 20th century, businessmen made their way into a coffee agriculture economy and mining, and for this reason, in addition to ensuring the sociopolitical and economic conditions that allowed their activities, they also had to work on their legitimation before society, and to do so they turned to already recognized painters and draftsmen to carry out the advertising of their companies, adding ideological content related to modernity and progress to their products, as the brands gained their visual distinctiveness. Thanks to this contribution, the artists also legitimized their profession as publicists and designers.